2016
DOI: 10.4103/0253-7613.178836
|View full text |Cite
|
Sign up to set email alerts
|

Contemplation on marking scheme for Type X multiple choice questions, and an illustration of a practically applicable scheme

Abstract: Ever since its inception 100 years back, multiple choice items have been widely used as a method of assessment. It has certain inherent limitations such as inability to test higher cognitive skills, element of guesswork while answering, and issues related with marking schemes. Various marking schemes have been proposed in the past but they are not balanced, skewed, and complex, which are based on mathematical calculations which are typically not within the grasp of medical personnel. Type X questions has many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…In present study, we analyses the effectiveness of MCQs and OSPE type of assessment in first year medical curriculum. 9 Our data showed that objective type of examinations results in to greater scoring over conventional type of method in theory and practical. In previous studies 10,11 authors observed that the score obtained in MCQs was similar to the score of SEQs and concluded that the students who performed well in the essay were also likely to do well in the MCQs.…”
mentioning
confidence: 62%
“…In present study, we analyses the effectiveness of MCQs and OSPE type of assessment in first year medical curriculum. 9 Our data showed that objective type of examinations results in to greater scoring over conventional type of method in theory and practical. In previous studies 10,11 authors observed that the score obtained in MCQs was similar to the score of SEQs and concluded that the students who performed well in the essay were also likely to do well in the MCQs.…”
mentioning
confidence: 62%
“…Credit will only be given at or above chance performance (≥ n /2 statements answered correctly). Additional fractional points are awarded as the number of correct answers increases Count ‐ 3: Compared to the Count‐2 approach, the minimum number of correct answers required for partial scoring might be increased and credit would be given only above chance performance (> n /2 statements answered correctly) …”
Section: Methodsmentioning
confidence: 99%
“…Additional fractional points are awarded as the number of correct answers increases Count ‐ 3: Compared to the Count‐2 approach, the minimum number of correct answers required for partial scoring might be increased and credit would be given only above chance performance (> n /2 statements answered correctly) “Vorkauf ‐ Method”: Half‐credit might be awarded even if only 1 answer is incorrect, otherwise 0 credit or 1 credit (full credit) is awarded …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations